Deteksi Boraks Dari Bahan Alami Ekstrak Kunyit Dan Penyuluhan Pada Ibu-Ibu Di Desa Sumber Jaya Kecamatan Timang Gajah Bener Meriah - Zulfikar; Aditama, Wiwit; Budi Arianto; Khairunissa; Arnida Sari (Poltekkes Kemenkes Aceh, 2022)
Foods are characterized as having substances that are unfit for consumption because they have elements that are damaging to health. the existence of studies conducted by the Food and Drug Supervisory Agency that revealed the presence of hazardous preservatives like borax and formalin in components used to make street food, including meatballs, wet noodles, and salted fish that is sold in the market. The entire sample (100%) yielded negative findings for the borax test. The formalin test findings on 25 samples of noodles revealed that all 25 samples (100%) contained formalin, with a level of 4.71 mg/L. Since March 2015, tests have been done on food distributed near Aceh Besar. 98 food samples were evaluated during those three months and borax testing results for 18 of them. Yellow noodles, batagor, and fried meatballs are typically the ones with dangerous ingredients. The goal of the activity is to teach moms how to identify the presence of borax and formalin in snacks and to make them aware of the risks these substances represent to their health. research techniques using counseling and demonstration. From July 22 through July 24, 2017, the event took place in Sumber Jaya Village, Timang Gajah District, Bener Meriah Regency. A total of about 30 moms who were in groups for routine recitation and mothers of toddlers participated in the therapy. Results To be more persuasive, a food test kit is delivered to compare the outcomes of turmeric extract with those from current tools. In this service, the demonstration uses tools, including making a straightforward turmeric extract using a blender and filter. The use of visual aids helps the audience understand the demonstration's workings because they can observe and analyze actual objects. Making extracts is a technique used by respondents in counseling. The purpose of the practical exercise was to give the participants practice identifying formaldehyde and borax. Keywords: borax, formaldehyde, turmeric